2020
DOI: 10.3390/electronics9060951
|View full text |Cite
|
Sign up to set email alerts
|

Automatic ECG Diagnosis Using Convolutional Neural Network

Abstract: Cardiovascular disease (CVD) is the most common class of chronic and life-threatening diseases and, therefore, considered to be one of the main causes of mortality. The proposed new neural architecture based on the recent popularity of convolutional neural networks (CNN) was a solution for the development of automatic heart disease diagnosis systems using electrocardiogram (ECG) signals. More specifically, ECG signals were passed directly to a properly trained CNN network. The database consisted of more than 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…The network classified five different kinds of anomalies with a detection accuracy of 92.7%. Avanzato et al [ 57 ] proposed an automatic heart disease diagnosis system using ECG signals based on the direct application of a 1D-convolutional neural network. The network consisted of three layers in addition to the input layer and the output layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The network classified five different kinds of anomalies with a detection accuracy of 92.7%. Avanzato et al [ 57 ] proposed an automatic heart disease diagnosis system using ECG signals based on the direct application of a 1D-convolutional neural network. The network consisted of three layers in addition to the input layer and the output layer.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the model achieved a significant classification accuracy and superior computational efficiency than most of the state-of-the-art methods for ECG signal classification. Avanzato et al [ 57 ] proposed a new neural architecture based on 1D-CNN for the development of automatic heart disease diagnosis systems using ECG signals. The model was performed on 30 s segments and classified three different classes of anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if the input matrix size to be convoluted is 5 × 5 and the convolution kernel size is Based on the above operation rules, the input signal is scanned with a convolution kernel of preset size and a convolution step size [26]; that is, the convolution kernel is used to cover an input signal region of the same size to perform the operation from the input to the corresponding position of the convolution kernel in the region, and the result is taken as a basic element of the convolution output. During the calculation of the convolutional layer, the size of the output image needs to be designed in each layer.…”
Section: Convolution Layermentioning
confidence: 99%
“…Deep learning models [ 4 , 5 , 6 , 7 ] are comparatively efficient in performing the classification process from the images and the data. There has been a demand in the field of healthcare diagnosis in precise identification of the abnormality and classifying the category of the disease from the X-ray, Magnetic Resonance Imaging (MRI), Computer Tomography (CT), Positron Emission Tomography (PET) images, and the signal data like the Electrocardiogram (ECG), Electroencephalogram (EEG), and Electromyography(EMG) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The precise identification of the disease category will assist in providing better treatment for patients.…”
Section: Introductionmentioning
confidence: 99%